2008
DOI: 10.1091/mbc.e08-06-0603
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule-mediated Src Tyrosine Kinase Trafficking in Neuronal Growth Cones

Abstract: Src family tyrosine kinases are important signaling enzymes in the neuronal growth cone, and they have been implicated in axon guidance; however, the detailed localization, trafficking, and cellular functions of Src kinases in live growth cones are unclear. Here, we cloned two novel Aplysia Src kinases, termed Src1 and Src2, and we show their association with both the plasma membrane and the microtubule cytoskeleton in the growth cone by live cell imaging, immunocytochemistry, and cell fractionation. Activated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
46
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(53 citation statements)
references
References 64 publications
7
46
0
Order By: Relevance
“…Thus, the dynamic positioning of PTP1B at the peripheral region of growth cones may contribute to the activation of Src. Using a membrane-targeted FRET sensor, we found that Src is active at the growth cone and filopodia, in agreement with previous immunodetection of phospho-active forms of Src (Robles et al, 2005;Wu et al, 2008). Interestingly, overexpression of PTP1B increased the FRET signal in the peripheral region and filopodia.…”
Section: Regulation Of Filopodial Dynamics and Src Activation By Ptp1bsupporting
confidence: 90%
See 4 more Smart Citations
“…Thus, the dynamic positioning of PTP1B at the peripheral region of growth cones may contribute to the activation of Src. Using a membrane-targeted FRET sensor, we found that Src is active at the growth cone and filopodia, in agreement with previous immunodetection of phospho-active forms of Src (Robles et al, 2005;Wu et al, 2008). Interestingly, overexpression of PTP1B increased the FRET signal in the peripheral region and filopodia.…”
Section: Regulation Of Filopodial Dynamics and Src Activation By Ptp1bsupporting
confidence: 90%
“…Recent work suggests that Src activity is required for filopodia initiation, extension, and dynamics (Robles et al, 2005;Wu et al, 2008). In addition, we and others have shown that Src activity is promoted by PTP1B in nonneuronal cells Bjorge et al, 2000).…”
Section: Ptp1b Regulates Growth Cone Dynamics and Src Activitymentioning
confidence: 67%
See 3 more Smart Citations